An Analysis of the Blank Ballot Phenomenon in the Maros Regency Local Elections - Saputra, Marham Haris; Asis, Patta Hindi; Lampassa, Yunitawati (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2025)
Since the 1998 Reformation, the development of democracy in Indonesia has made significant progress, despite facing challenges in implementing general elections, especially in the context of the empty box phenomenon. This research aims to analyze the factors that influence low voter participation in the 2024 Maros Regency Pilkada, as well as the implications for local democracy. The research method used was descriptive qualitative with data collection through purposive sampling, involving 10 informants from various backgrounds. The research results show that dissatisfaction with a single candidate, lack of political awareness, and lack of outreach from organizers are the main factors causing a decrease in voter participation. In addition, the empty box phenomenon reflects people's dissatisfaction with the available options, which has the potential to reduce democratic legitimacy. This research recommends the need for strategic steps to increase voter participation, including political education and support for diverse and competent candidates.